Single stage dimethyl ether plant model based on gasification of palm empty fruit bunch. (May 2019) - Heryadi, R; Uyun, A S; Yandri, E; Nur, S M; Abdullah, K
Abstract: Biomass from empty fruit bunch (EFB) is considered as potential renewable energy sources to be developed in Indonesia. EFB can be efficiently converted into valuable and useful fuel products through gasification. Gasification is a process of biomass conversion into syngas. Syngas is a raw material for most other chemical products, such as Methanol, Ammonia, and DME. One of the biomasses that has big potential to be utilized is palm EFB waste. Research about DME synthesis from various biomass has been done, though little research about DME production based on EFB gasification. The aim of this research is to simulate single stage DME Plant Model based on gasification of EFB by assuming that the gasification reaction and DME synthesis reaction are under equilibrium condition. Method encompasses step to perform simulation of the model and DME plant design. The model predicts yield of DME product in agreement with published real DME plant operation. The result shows flow rate of DME produced is 50% of EFB feed flowrate and 73% energy efficiency obtained for pre-treated EFB. Electric power requirement has been investigated at 4096 kW and can be fulfilled by DME Plant through steam generation cycle and internal combustion engine fuelled by DME product. The model developed will be used as a basis for techno-economic analysis of DME plant based on EFB gasification.